O direito adquirido processual e as leis 9.756/98 e 11.672/08: recursos especiais retidos e repetitivos. - Nascimento Netto, Marcos Aurélio (2010)
Legislative alterations concerning lodgeable appeals cannot affect the vested procedural right of a litigant who already has an impugnable legal proclamation against him. Although the plaintiff have not executed the appropriate [legal] appeal, it can be undertaken in accordance with the rules previously in vigour, since these rules are already incorporated into the plaintiff’s legal right(s). The immediate application of the procedural law does not infringe on consolidated cases in pending suits owing to the irretroactivity principle of laws. Regarding Special Appeals, the law which created a regime to withhold appeals, in addition to the law which altered its procedure (for repetitive appeals), cannot affect the impugnations of previously published legal decisions.